Customary Penalty Sanctions for Adultery Crimes in Temon Village, Arjosari District, Pacitan Regency - Arief Budiono; Erlin Reniawati; Mira Anjar Oktaviani (Universitas Ahmad Dahlan, 2018)
Today, some Indonesian still adhere to the customs that come from their respective regions. It also includes habits that are carried out repeatedly which becomes a rule or commonly referred to customary law. Based on the philosophical aspect of customary law that lives, grows and develops in the soul of the Indonesian people in accordance with the values of the Pancasila as stated in the opening of the 1945 Constitution, the existence of customary law is very influential on customary crimes that occur in certain regions. Customary violations are still commonly found in the community, especially adultery. The implementation of customary criminal sanctions is felt to provide satisfaction and a sense of justice for some people so that the people’s lifes can be balanced.